"Genius Loci - muzeum biograficzne Jana Matejki, różne aspekty działalności" = "Genius Loci - the biographical museum of Jan Matejko, the various aspects of activity" - Kłak-Ambrożkiewicz, Marta (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
After the death of Jan Matejko (1838-1893) the idea of founding a biographical museum in his house arose. In 1904, the building became a branch of the National Museum in Krakow. The institution, apart from conducting research on the life and work of the artist, deals with various forms of popularization of this knowledge. Exhibitions, popular science lectures like"Thursdays at the Matejko family", "Meeting with the curator", are only part of them.
Keywords: malarz; genius loci; muzeum biograficzne; popularyzacja; muzykowanie; painter; biographical museum; popularization; musicmaking